The transient response of multiferroic composites. (March 2018) - Aboudi, Jacob
Abstract: The transient response of multiferroic magnetoelectric composite materials which consist of electro-magneto-thermo-elastic phases is determined. This response is governed by the fully coupled constitutive relations, according to which the electro-magneto-elastic field affects the temperature and vice versa, as well as the dynamic equations of motion, Maxwell and energy. The method of solution is based on the discretization of the composite domain into subcells in everyone of which the governing equations are imposed in the average (integral) sense. The interfacial and boundary conditions are also imposed at the average sense. The validity of the offered method of solution is examined in four special cases where analytical solutions can be established. The proposed approach is implemented on a three ceramic layered composite strip whose transient response is determined under various types of time-dependent loading. Comparisons between the responses based on the transient and quasi-static solutions are shown.